2017
DOI: 10.1016/j.maturitas.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in use of time across retirement: A longitudinal study

Abstract: Objectives. This study aimed to investigate how daily use of time changes across the retirement transition and how these changes may differ according to socio-demographic characteristics.Study design. This longitudinal cohort study was based on interviews with 124 people at preretirement and at three, six and 12 months after retirement. Main outcome measures. The Multimedia Activity Recall for Children and Adults(MARCA), a computer-assisted telephone interview, measured use of time. Random effects mixed modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
41
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 25 publications
8
41
1
Order By: Relevance
“…Although reinforcing the findings of increased sleep duration and decreases in waking up too early in the morning, nonrestorative sleep, and daytime tiredness from the previous studies [1-3, 5, 6], the results from this study indicate that the changes in various sleep characteristics begin to occur immediately or shortly after retirement. Indications of these quick changes in the case of sleep duration were already described by an Australian study, which examined time use across retirement transition and observed that 3 months postretirement approximately 30 min more time per day was used for sleeping than before retirement [27]. Furthermore, the estimates of increased sleep duration from the previous studies with longer measurement intervals [1,2] are very close to the 19-min increase observed in this study with a dense measurement interval around retirement.…”
Section: Discussionsupporting
confidence: 85%
“…Although reinforcing the findings of increased sleep duration and decreases in waking up too early in the morning, nonrestorative sleep, and daytime tiredness from the previous studies [1-3, 5, 6], the results from this study indicate that the changes in various sleep characteristics begin to occur immediately or shortly after retirement. Indications of these quick changes in the case of sleep duration were already described by an Australian study, which examined time use across retirement transition and observed that 3 months postretirement approximately 30 min more time per day was used for sleeping than before retirement [27]. Furthermore, the estimates of increased sleep duration from the previous studies with longer measurement intervals [1,2] are very close to the 19-min increase observed in this study with a dense measurement interval around retirement.…”
Section: Discussionsupporting
confidence: 85%
“…Other research has also reported increases in computer use/screen time and TV after retirement [14][15][16][17][18][19]. In our study, prolonged sitting for TV-viewing increased from 11.8% to 16.5% in men and from 10.2% to 13.2% among women.…”
Section: Discussionsupporting
confidence: 65%
“…The sex differences in time allocation regarding home-based activities are in line with previous research by Adjei and Brand that was conducted in Germany [9], as well as Sprod et al that was conducted in Australia [11,29], who also found that women spend more time on housework but less on gardening than men. Gauthier and Smeeding [12] reported the same ndings for overall home-based activities in nine different countries, but, contrasting our results, saw a decrease with age in women devoting time to housework and an age-related increase in men.…”
Section: Discussionsupporting
confidence: 90%
“…While our ndings suggest that active transport is the domain older adults devote the least amount of time on, several other studies reported leisure PA to be the domain the least time is spent on [11,12,29,30]. Sprod and colleagues [11,29] also made a distinction between active and inactive travel and reported almost three times more minutes per day being spent on it than our study. These differences could be a result of us only using everyday destinations, whereas Sprod et al included every destination.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation